Aspek Perkembangan Manajemen Pembelajaran Active Learning, Paikem Pada Kelas Unggulan - Tanya Fawzi; Limas Dodi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to describe the management of Active Learning, PAIKEM for excellence students at Madrasah Ibtidaiyah Miftahul Huda with a research focus on supporting resources for successful curriculum implementation in excellence classes at MI Miftahul Huda Kayen Kidul. Implementation of School Management and Active Learning Learning Strategies at MI Miftahul Huda Kayen Kidul. Utilization of Learning Resources, Use of Learning Media and Monitoring of Curriculum Implementation at MI Miftahul Huda Kayen Kidul Kediri. The method used in this research is descriptive qualitative method. The results of this study are: there are three supporting resources for the success of MI Miftahul Huda's excellence class curriculum management, namely school management from the Madrasah principal regarding new innovations in excellence classes in the compulsory learning process using English and applying Active Learning in the learning process. Learning Resources do not use modules but CPS (Comprehension and Project Sheet) in English and Learning Media according to the material. The implementation of school management is planning, organizing, implementing and evaluating in excellence classes as well as learning methods used such as Role Playing, Jigsaw. Utilization of learning resources using natural spring according to subjects, English books. Learning media using LCD, paper. As well as for monitoring, namely after the learning process there is an evaluation of the excellence class handling the learning process and student outcomes in the excellence class according to the curriculum used.